Generative Mechanisms for Digital Platform Ecosystem Evolution - Kalina S. Staykova (Copenhagen Business School (CBS), 2019)
Despite their growing economic importance and rapid proliferation across various industries, successful digital platform ecosystems remain difficult to build and sustain over time. Facing challenges stemming from the turbulent and uncertain environment, in which they operate, and from the accumulated over time internal inefficiencies, digital platform ecosystems need to evolve and adapt rapidly. Despite the importance of understanding how and why this evolutionary process occurs, research on this topic has remained elusive. Building upon the notion of generative mechanisms, this PhD dissertation seeks to unravel the various mechanisms, which contingently shape the evolution of digital platform ecosystems. To this end, this research investigates the evolutionary process from three theoretical perspectives – Punctuated Equilibrium, Dialectical and Teleological, and by adopting multi-method approach. As a result, the PhD dissertation puts forward three process theories, each characterized by distinctive generative mechanisms, which collectively provide in-depth insights how digital platform ecosystems evolve over time in response to internal and external challenges.
hdl:10398/9707
Keywords: 650